Maurício Wellisch: A Forgotten Modern in Brazil - Martinho Alves da Costa Junior (Athens Journal of History, 2024)
This article aims to give visibility to the work of Maurício Wellisch (1904-1961). An artist active in the first decades of the 20th century, Wellisch stood out especially with his illustrations. He participated in exhibitions as a painter and was a prolific chronicler and critic of the arts. Graduated in law in 1925, he soon embarked on a political career, working continuously at Itamaraty. A career diplomat, he served in numerous cities, such as Antwerp, Prague, etc. During this period, he moved away from his brushes, remaining, however, faithful to writing in a continuous approach to culture and arts in the places he visited. For this work we will focus the analysis on two periodicals, Phoenix and Boletim de Ariel. The first, published between 1924 and 1926, whose proposal was to establish a direction, perceive and act in a post-war world, rising from the ashes through the arts. In addition to Wellisch, the periodical was illustrated by Ismael Nery, Oswaldo Teixeira, A, Voigt, Lleux, among others. In specific cases like Lleux or Voigt the aesthetic is close to that of Mauricio Wellisch.